Effect of polythene mulches and barrier crops on virus disease incidence and yield of bell pepper - KAPOOR*, PROMIL (Indian Phytopathology, 2012)
Bell pepper (Capsicum annuum L.) is one of the important commercial vegetable crops belonging to the nightshade or solanaceae family. In Himachal Pradesh while conducting regular surveys for the presence of different diseases in vegetables, most of the bell pepper cultivating localities were found to suffer due to infection of virus(es) on this crop with a disease incidence as high as 100 per cent. Field experiments were conducted over two growing seasons to determine the effect of different coloured mulches and planting of maize as barrier crop on virus disease of bell pepper. Amongst the different coloured mulches tested, silver (polyester sheet) followed by white polythene mulch showed minimum virus disease incidence and maximum average yield per plot thus, proved better than the white, yellow, blue, black and green coloured mulches used. Planting of maize as a barrier crop was also found effective in reducing virus disease incidence and increasing the yield of bell pepper. Minimum disease incidence was observed when maize was planted as border row plus as an intercrop in the middle of the plot. Hence, both the cultural management practices resulted in lowering the virus disease incidence and increasing the average yield per plot in comparison to control.